2020
DOI: 10.1007/s12652-020-01926-y
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing the kinematic and kinetic contributions of the human upper body’s joints for ergonomics assessment

Abstract: During an eight-hour shift, an industrial worker will inevitably cycle through specific postures. Those postures can cause microtrauma on the musculoskeletal system that accumulates, which in turn can lead to chronic injury. To assess how problematic a posture is, the rapid upper limb assessment (RULA) scoring system is widely employed by the industry. Even though it is a very quick and efficient method of assessment, RULA is not a biomechanics-based measurement that is anchored in a physical parameter of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 21 publications
1
7
0
Order By: Relevance
“…Based on the identified range and the imposed implementation constraints, the joint range of 116 • (θ max ) was considered. This range was also in accordance with former studies on occupational ergonomics [19], [20]. For this joint range, the necessary tendon length (l f ) for the flexion and the extension movements was approximately 178 mm using (4):…”
Section: A Torque and Motion Range Of The Elbowsupporting
confidence: 88%
“…Based on the identified range and the imposed implementation constraints, the joint range of 116 • (θ max ) was considered. This range was also in accordance with former studies on occupational ergonomics [19], [20]. For this joint range, the necessary tendon length (l f ) for the flexion and the extension movements was approximately 178 mm using (4):…”
Section: A Torque and Motion Range Of The Elbowsupporting
confidence: 88%
“…An ergonomic analysis using such an approach can result in over-simplicity and ignore other potential risks workers are exposed to (e.g., external forces and dangerous movements). Menytchas [ 17 ] expanded such ergonomic analysis by examining the kinematics and kinetics of professional movements to identify joints that accumulate the most strain. The kinetic descriptors used in that study, however, did not allow for accurate discrimination between dangerous motions with small variations in the posture; moreover, they do not analyze the dynamics of movements, unlike the present study, which allowed for a good recognition performance and distinction between motions of different ergonomic risk.…”
Section: Discussionmentioning
confidence: 99%
“…Most previous studies have used biomechanical modeling to extract the kinematic and kinetic contributions of the joints, in diverse motor tasks, then investigate the mechanical loading of the joints and their response to ergonomic interventions. To analyze the ergonomic impact of different postures on human joints, Menychtas et al [ 17 ] applied the Newton–Euler algorithm for the computation of upper body joint torques. The normalized integral of joint angles and joint torques was then calculated to describe the kinematic and kinetic contribution of the body joints when awkward poses are assumed.…”
Section: State-of-the-artmentioning
confidence: 99%
“…For example, Malik et al [10] utilized a DH simulation for ergonomic assessment of the workspace layout based on visual and grasp analyses. Furthermore, Menychtas et al [35] demonstrated the effectiveness of joint torque analysis for evaluating the physical load on industrial workers.…”
Section: Ergonomic Assessment In Industry Fieldsmentioning
confidence: 99%